Effect of different housing systems on physiological, ethological and growth performances of crossbred (Hampshire X Tenyi Vo) pigs in Nagaland - Leeford Cliff Lyngkhoi; M Catherine Rutsa; VK Vidyarthi; J Longkumer; Rokonituo Nakho (Journal of Livestock Biodiversity, 2025)
Experimental study on the effect of different housing system on the physiology, ethology and growth performance of Hampshire X Tenyi Vo cross bred pigs in Nagaland using twenty one weaned pigs of forty two days old irrespective of sex were undertaken. The animals were divided into three groups and reared under three housing systems viz. Standard housing with wooden floor (T1), concrete floor (T2) and indigenous housing with concrete floor (T3). The piglets' behavioural activities were recorded and the data showed that animals in T1 spent more time in feeding and drinking while T2 spent more time in resting. The animals reared in standard housing with wooden floor recorded the highest rectal temperature of 38.730 C as compared to the animals reared in standard housing with concrete floor. The respiratory rate of the Upgraded Tenyi Vo under treatment did no differ significantly and is within the normal range. The average body weight of the animals at the end of the study were recorded as 8.79, 10.50 & 9.84 Kg for T1, T2 and T3 respectively, with no significant difference in the average daily gain of the animals under treatment. Hampshire X Tenyi Vo cross bred pigs reared in standard housing with concrete floor showed improvement in the overall body weight gain.